Analisa Terhadap Penerimaan Dan Penggunaan Perpustakaan Digital Berdasarkan Pendekatan Utaut : Studi Kasus Perpustakaan STMIK MIC CIKARANG - Muhtajuddin Danny (Jurnal SIGMA, 2021)
Digital Library is a product of the integration of the progress of Information and Communication Technology (ICT), which provides scientific information to library users. Site www.mic.ac.id/lib is STMIK MIC library CIKARANG which has been providing digital library services. This study aims to assess the behavior of library users STMIK MIC CIKARANG based on the factors that influence the approach to Unified Theory of Acceptance and Use of Technology (UTAUT), using analysis of Structural Equation Modelling (SEM) by Analysis of Moment Structure (AMOS) as a software data processing applications. This study uses a quantitative approach Explanative survey method. The student population is STMIK MIC CIKARANG. Sampling using purposive sampling, with as many as 118 respondents evaluated through a questionnaire. In the partial test showed that the variables Behavioural Intentions has a positive and significant correlation with Behavovioural Use (p-value <0.05). While Performance Expactancy, Social Influence, Facilitating Conditions did not have a significant correlation with Behavioural Intentions. Keywords: Digital Library, UTAUT, AMOS.